2014
DOI: 10.1002/jcp.24601
|View full text |Cite
|
Sign up to set email alerts
|

PPARγ and RXR Ligands Disrupt the Inflammatory Cross-talk in the Hypoxic Breast Cancer Stem Cells Niche

Abstract: Cancer stem cells (CSCs) are affected by the local micro-environment, the niche, in which inflammatory stimuli and hypoxia act as steering factors. Here, two nuclear receptors (NRs) agonists, i.e. pioglitazone (PGZ), a ligand of peroxisome proliferator activated receptor-γ, and 6-OH-11-O-hydroxyphenanthrene (IIF), a ligand of retinoid X receptors, were investigated for their capability to interference with the cross-talk between breast CSCs and the niche compartment. We found that IIF potentiates the ability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 56 publications
(101 reference statements)
2
42
0
2
Order By: Relevance
“…To our knowledge, this is the first article to examine the effect of PPARγ activation on HIF-1α signaling in HPASMCs. PPARγ activation reduced expression of HIF-1α in cancer stem cells 46 and increased HIF-1α in breast cancer cells, 47 whereas both transcription factors were upregulated in cardiac hypertrophy. 48 We previously reported that RSG attenuated HIF-1α activation in hypoxic endothelial cells, 31 and pioglitazone similarly attenuated HIF-1α in skeletal muscle through effects on mitochondrial function.…”
Section: Discussionmentioning
confidence: 98%
“…To our knowledge, this is the first article to examine the effect of PPARγ activation on HIF-1α signaling in HPASMCs. PPARγ activation reduced expression of HIF-1α in cancer stem cells 46 and increased HIF-1α in breast cancer cells, 47 whereas both transcription factors were upregulated in cardiac hypertrophy. 48 We previously reported that RSG attenuated HIF-1α activation in hypoxic endothelial cells, 31 and pioglitazone similarly attenuated HIF-1α in skeletal muscle through effects on mitochondrial function.…”
Section: Discussionmentioning
confidence: 98%
“…IIF also induced differentiation in several cancer cell lines, inhibited MMP-2 and MMP-9 and increased expression of their inhibitors (TIMP-1 and TIMP-2) [44]. Both ATRA and IIF down-regulated genes that supported the tumour stem cell phenotype maintenance (Slug, Notch-3 and Jagged-1) by blocking the NF-κB axis: these events were associated with re-expression of differentiation markers such as ERα and keratin-18 in breast carcinoma stem cells [45]. …”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, hypoxia-mediated triggering of HIF-1α (Hypoxia inducible factors) enhanced exosomes secretion and lead to aggressive cell phenotype [67]. Breast cancer-derived exosomes produced under hypoxic conditions can also promote inflammatory crosstalk within the tumor niche to promote growth, which is decreased by activation of nuclear receptors within the cancer cell [68]. Besides, tumor cells made cancer cells significantly reduce the effectiveness of irradiation under hypoxic tumor microenvironments.…”
Section: Exosomes Influence On Tumor Growth Under Hypoxic Environmentmentioning
confidence: 99%